K. wire fixation versus conservative treatment of closed displaced intra-articular calcaneal fractures - Al-Edanni, Mohammed Sh. (AL-Kindy College Medical Journal, 2019)
Background: Calcaneus is a spongy cancellous bone with rich blood supply , its fracture heals more rapidly providing no occurrence of infection and soft tissue injury around ,no gross malposition of fragments. The associated pain leads to a major impairment in life quality. The aim of treatment for calcaneal fractures is the decrease of pain and rebuilding of walking ability for patients with normal foot shape and the ability to wear normal foot wear. To reduce complications, a minimally invasive technique for the treatment of displaced intra-articular fractures of the calcaneus was preferred to use.The purpose of this study was to determine whether the closed reduction and percutaneous K. wire fixation of displaced intra-articular calcaneal fractures results in better functional outcome at a minimum one year follow up after the injury compared with those after non-operative management.Methods: One hundred and eleven displaced closed intra-articular calcaneal fracture in 105 patients (six were bilateral) were seen at the orthopedic department of Al-Kindy teaching hospital and Shaih Zaid hospital , only 45 cases included in this study and prospectively evaluated with an average follow-up time of minimum  of one year (1–3years follow-up). For radiographic evaluation, plain radiographs and CT scans were obtained. The Maryland Foot Score was used for clinical estimate. Sanders type II, III and IV fractures were diagnosed.Results: The incidence of subtalar arthritis was correlated with the severity of fracture. Böhler’s angle was restored in 70.1% (47 of 67) of the cases. The majority (77.7%) of patients were content with their treatment result. The rate of significant complications was 6.5%.Discussion: Percutaneous K. wire fixation of displaced intra-articular calcaneal fractures presented minimally invasive technique which showed comparable results with a low rate of serious complications and is a viable alternative for the treatment of intra-articular, dislocated calcaneal fractures.Conclusions: the functional results after K. wires fixation of displaced intra-articular calcaneal fractures were better than those after non-operative care.